Novel Fish Predator Causes Sustained Changes in Its Prey Populations - Nõomaa, Kristiina; Kotta, Jonne; Szava-Kovats, Robert; Herkül, Kristjan; Eschbaum, Redik; Vetemaa, Markus (Frontiers in Marine Science, 2022)
Ecosystems are simultaneously regulated by bottom-up (resources) and top-down forces (predators). However, because predator-prey interactions operate on spatial scales beyond the reach of manipulative experimentation, the actual roles of predators remain poorly understood. In ecosystems where predators are naturally absent, biological invasions provide a unique experiment to shed light on the large-scale and long-term effects of predators in the recipient ecosystem. We combined data from long-term benthic monitoring, environmental conditions, and a census of round goby population to identify changes in the dominant benthic bivalve population (Mytilus trossulus and Macoma balthica) following round goby (Neogobius melanostomus) invasion. This study demonstrates a substantial change in the food web, with earlier primarily bottom-up regulated communities facing strong top-down control effects. The introduction of a novel predator to a species-poor ecosystem substantially reduced dominant invertebrate populations in a large part of the study area, sometimes with a time lag of 1−3 years. In general, the effects were less in high productivity areas. In some cases, community recovery was observed but rarely to pre-invasion levels, raising the question of the ability of bivalve communities to act as a natural filter. This study demonstrates long-term trends in benthic communities and by excluding possible effects due to the changing environment provides more evidence that invasive species transform coastal ecosystems over time and space.